Safety, tolerability and pharmacokinetics after single and multiple doses of preladenant (SCH420814) administered in healthy subjects. - Cutler, D. L.; Tendolkar, A.; Grachev, I. D. (Journal of Clinical Pharmacy & Therapeutics, 2012)
What is known and Objective: Preladenant (SCH420814, MK-3814) is a highly selective orally bioavailable non-methylxanthine adenosine 2A (A2A) receptor antagonist under investigation for the treatment for Parkinson's disease. This study evaluated the safety, tolerability and pharmacokinetics of preladenant at single and multiple doses for the first time in humans. Methods: These were two randomized, double-blind, placebo-controlled, ascending-dose studies, one evaluating single rising preladenant doses (5-200 mg) compared with placebo and the other evaluating multiple rising preladenant doses (10-200 mg once daily over 10 days) compared with placebo. Safety was the primary end point of both studies. Safety evaluations, physical examinations, electrocardiograms, vital signs determinations and routine laboratory tests were performed before and at intervals throughout the studies. Blood samples were collected immediately before study drug administration and at various time points after dosing. Pharmacokinetic assessments of plasma preladenant and metabolites SCH434748 and SCH446637 were performed. Results and Discussion: One hundred and eight healthy adult men were randomly assigned in a 3 : 1 ratio to receive oral preladenant or matching placebo capsules under fasting conditions. Preladenant reached peak plasma concentrations in ∼1 h and then declined rapidly. Dose-related increases in exposure were observed up to 100 mg/day; accumulation was negligible at all doses. Transient mild increases in blood pressure occurred within a few hours after preladenant administration; blood pressure changes were neither cumulative nor dose-related nor associated with clinical sequelae. What is new and Conclusion: Preladenant was generally well tolerated up to the maximum dose tested (200 mg/day).